Delirium: medical students’ knowledge and effectiveness of different teaching methods - Baessler, Franziska; Ciprianidis, Anja; Rizvi, Ali Z.; Weidlich, Joshua; Wagner, Fabienne L.; Klein, Sonja B.; Baumann, Tabea C.; Nikendei, Christoph; Schultz, Jobst-Hendrik (American journal of geriatric psychiatry, 2019)
Objective - Medical schools are often blamed for inadequately training doctors on delirium. This study assesses the knowledge of medical students regarding delirium and evaluates different teaching methods for comparing learning outcomes. - Methods - A video, a handout, and a video+handout were used as three different teaching methods. Students were randomly assigned to three groups and pre- and postintervention knowledge gains were compared. Interventions were held between 2015 and 2018 at the University of Heidelberg Medical School in Germany. Seventy-eight (video intervention 33; handout 26; video+handout 19) sixth-year medical students participated. Participants learned about delirium with the help of a video, a handout, and both a video+handout at the start of one-hour lectures dedicated to teaching about delirium. Pre- and postintervention questionnaires, comprising five multiple-choice questions and a self-estimated grade of knowledge about delirium, were used. Variables calculated were objective and subjective knowledge, recall, and accuracy of self-assessment. Microsoft Excel and analysis of covariance were used to analyze data. - Results - Knowledge gains for all interventions were large (d>0.8) irrespective of gender. Post hoc comparison showed video and video+handout methods were more effective with high recall for video (92.8%). Students rated their knowledge as satisfactory, although they scored 11.4 out of 20. Preintervention knowledge level was correctly estimated by 31% of students, and postintervention by 40.3% students. - Conclusion - Teaching about delirium to medical students with a video resulted in better knowledge transfer and recall. Most medical students, particularly men, overestimated their knowledge about delirium.
Gesehen am 04.12.2019